Psychological “Risks” of Colonoscopy are Greater Amongst Fecal Immunohistochemical Test Positive Individuals than those with Inflammatory Bowel Disease - Mountifield Réme; M Andrews Jane; Prosser Ruth; Mikocka-Walus Antonina; Bobridge Amanda; Bampton Peter (Journal of Colon And Rectal Cancer, 2016)
Background: Colorectal cancer (CRC) screening by Fecal Immunohistochemical Testing (FIT) followed by colonoscopy reduces colorectal cancer mortality. Barriers to colonoscopy should be minimised. Objective: To compare psychological “risks” of colonoscopy in FIT positive (FIT+) subjects and those with Inflammatory Bowel Disease (IBD). Method: IBD patients undergoing colonoscopic CRC surveillance were age and gender matched with FIT+ individuals awaiting colonoscopy. Subjects completed Spielberger State and Trait Scales for current levels of anxiety, depression, anger and curiosity, versus long term personality tendencies. Results: 70 IBD respondents were matched with 70 FIT+ respondents, (57% male, mean age 57.6 years). FIT+ subjects demonstrated greater scores for state Anxiety (22.3 vs 20.3 p=0.024), Curiosity (24.3 vs 21.8 p=0.036), Anger (13.7 vs11.5 p=0.037) and Depression (23.8 vs21.2 p=0.002). Conclusion: FIT+ patients experience more anxiety and depression prior to their colonoscopy than IBD patients, which may reduce colonoscopy uptake and is important to address.
Keywords: Colorectal Cancer Screening / Surveillance